Domestic Crime and Methods of Its Prevention at Barangay San Agustin, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Domestic crime, also called domestic violence, is an act of violent abuse directed at a partner,family, or other relationship status. Usually, women are the victims of domestic crime becausethey are physically weaker than men and are the ones who are subjected to such treatment oraction. The common reasons for a person committing domestic crime or violence are that theyare angry, that they cannot control themselves from hurting the person they have hurt, or thatthey are drunk and unaware of what they have done. Nowadays, domestic crime or violence isrampant in many areas. The number of cases of domestic violence is increasing, particularlyas the COVID-19 pandemic spreads throughout the Philippines. The researchers want tostudy the causes of domestic crime or violence, the effects it has on victims, and the variousmethods of preventing it, as well as how effective they are in implementing it in Barangay SanAgustin, Quezon City. The qualitative descriptive will be used in the study.According to the findings of the study, the profile of the respondents is in terms of age; themajority of them are aged 18 and below, are female, single, and have an educationalattainment of high school level. As respondents describe domestic crime in terms of physicalabuse, the highest weighted mean is "Inflicting physical harm," which resulted in anagreement. As respondents describe sexual abuse, the highest weighted mean is "Usingforce, coercion, guilt, or manipulation or failing to consider the victim's desire to have sex,"which resulted in agreement in verbal interpretation. In terms of respondents' descriptions ofemotional abuse, "consistently disregarding, ignoring, or neglecting the victim's requests andneeds" received the highest weighted mean with agree in verbal interpretation; in terms ofverbal abuse, "threatening to hurt or kill the victim or her children, family, pets, property, orreputation" received the highest weighted mean, and in terms of the problem encountered inthe method of prevention, "Lack of understanding and awareness of domestic crime methodsof prevention" received the highest weighted mean as agree in verbal interpretation.The researchers recommended that Barangay officials develop a better action plan toincrease public awareness and understanding of domestic violence as well as the signs ofabuse. Citizens must be interested in learning about domestic violence and the signs of abusein order to be aware of it and prevent some probleMs. Criminology students study domesticcrime and are aware of domestic crime and abuse in order to have knowledge andunderstanding of these types of crime. Victims must be aware of the methods for preventingdomestic violence in order to avoid the events they have witnessed.
Keywords: Criminology